PENGARUH FAKTOR LINGKUNGAN DAN PERILAKU MASYARAKAT DENGAN KEJADIAN DBD DI SIBOLGA TAHUN 2020 - SIMANJUNTAK, RIDAWANI (Jurnal Inovasi Kesehatan Masyarakat, 2021)
DHF in Indonesia is an emerging disease with an increasing incidence from year to year. DHF attacks can have widespread consequences that can cause material and moral damage and the most fatal can result in loss of life or death. The purpose of this study was to determine the effect of environmental factors and people's behavior on the occurrence of Dengue Hemorrhagic Fever in Sibolga City in 2020. This type of research is case control design. Sample was 112 people. Samples were taken by simple random sampling method. Data collection was carried out using questionnaires and observations. The test used is multiple logistic regression test. The results of the study are there are effects of water reservoirs on the occurrence of Dengue Hemorrhagic Fever, Odd Ratio (OR) value = 14,824. There is an influence of residential density on the occurrence of Dengue Hemorrhagic Fever, Odd Ratio (OR) value = 10.501. There is an influence of the presence of gauze on the ventilation of the house to the incidence of dengue fever, the value of the Odd Ratio (OR) = 9,923. There is an effect of container index (CI) on the occurrence of Dengue Hemorrhagic Fever, Odd Ratio (OR) value = 23,699. There is an influence of the habit of hanging clothes on the occurrence of Dengue Fever, the value of Odd Ratio (OR) = 10.542. There is an influence of PSN habits on the occurrence of Dengue Hemorrhagic Fever, Odd Ratio (OR) value = 21,414. There is an influence of knowledge on the occurrence of Dengue Fever, the value of Odd Ratio (OR) = 12,128. There is an effect of action on the occurrence of Dengue Hemorrhagic Fever, Odd Ratio (OR) value = 9,711, Increasing efforts to eradicate Dengue Hemorrhagic Fever (PSN-DBD) mosquito nests such as draining / cleaning places that are often used as water reservoirs, closing water reservoirs such as drums, jugs, water torens, etc.; and reuse or recycle used goods that have the potential to become breeding grounds for dengue-infecting mosquitoes